Optimizing family's understanding and attitude about malnutrition and antropometry measurement based on family centered nursing - Melinda Restu Pertiwi; Diana Hardiyanti; Heryyanoor Heryyanoor (Universitas Muhammadiyah Magelang, 2022)
This programmatic community service activity for families with toddlers was conducted out in Sungai Tuan Ilir Village, Astambul District, Banjar Regency. In order to avoid cases of malnutrition in the family and community, increased understanding of malnutrition and anthropometric measurements must be optimized. Socialization in the form of group and individual health counseling in the family environment with a family centered nursing approach about malnutrition and anthropometric measurements, training on anthropometric measurements, and the application of growth curve measurements are among the activities carried out in community service. Community service can help families comprehend and adjust their views, especially when it comes to preventing malnutrition while doing family tasks and functions.